Marketing Analysis of Groundnut and Maize in Tongkuno District, Muna Regency - La Ode Dasrin; Surni, Surni; Yusna Indarsyih (International journal of technology and education research, 2025)
This study aims to analyze the marketing channels of peanuts and corn in Tongkuno District, Muna Regency, to analyze the size of the marketing margin, and the profits obtained by peanut and corn traders in Tongkuno District, Muna Regency, and to analyze the level of efficiency of marketing peanuts and corn in Tongkuno District, Muna Regency. The determination of the research location was carried out by simple random sampling with a total of 41 respondents. Data analysis using descriptive qualitative analysis, marketing margin, profit, and marketing efficiency. The results of the study obtained 1 peanut and corn marketing channel that is homogeneous, namely from farmers to retailers. And in this marketing channel, farmers only spend costs in each form of cost per kilogram, namely packaging costs for peanuts of Rp40.12/Kg, while for corn Rp40.00/Kg, transportation costs for peanuts of Rp340.12/Kg, while for corn Rp308.00/Kg, the cost of tax retribution for peanuts is Rp45.34/Kg, and for corn Rp41.05/Kg, the cost of storage for peanuts is Rp66.13/Kg while for corn Rp60.00/Kg. The average purchase price of peanut and corn retailers is Rp22,385/Kg for the Bali price of peanuts while for corn Rp5,385/Kg. for the average selling price of peanuts is Rp25,308/Kg and corn Rp7,500/Kg. So the results of the study show that the marketing channels for peanuts and corn in Tongkuno District, Muna Regency are efficient. So the Farmer share value of peanut marketing is 89% and for corn is 72%.